Penerapan Sistem Pendukung Keputusan (DSS) dalam Manajemen Pemeliharaan Perkerasan - Sri Wiwoho Mudjanarko; Arthur Daniel Limantara; Bambang Subiyanto; Fauzie Nursandah (CAHAYAtech, 2020)
Pavement maintenance for the road network in Surabaya does not yet have a scientific basis such as monitoring and evaluation.This study illustrates the possibility of applying a Decision Support System (DSS) in pavement maintenance management to evaluate the asphalt pavement surface conditions. Common types of Asphalt Concrete pressures include (Asphalt hemorrhage, various pavement cracking modes, pot holes, longitudinal and transverse deformations) with various conditions of severity and intensity included in the system database, mathematical models for calculating severity and levels for each type of distress as well entered. This software was developed in the Microsoft Visual Basic environment using a logic programming process. The pavement condition rating (PCR) of the road section will be determined by the system. The system suggests necessary maintenance actions based on an estimated increase in pavement age and on the cost of alternative treatments. This system is examined in evaluating the asphalt pavement surface conditions of the freeway to Juanda International Airport. Traditional visual inspection and manual calculation procedures have also been carried out. The sidewalk surface is divided into sections, and the sidewalk condition is visually visible Evaluated and assessed using specially designed forms, ranking is in the range (26-93)% representing "very bad to very good" conditions for the road section based on the ranking index provided . Data is entered into the decision support system software developed. The results are very much in accordance with the results of software development. It was concluded that the Decision Support System developed, can help planners, or policy makers to support decision making in the maintenance of pavement.